Influence of Concrete Compressive Strength on CFRP Strengthening and Repairing of RC Two-Way Slabs - Mohammed F. Ojaimi; Meyyada Y. Alabdulhady; Kadhim Z. Naser (Journal of Engineering)
In this research, the feasibility of strengthening and repairing two-way reinforced concrete slabs and the effect of compressive strength on the properties of strengthened and repaired slabs using CFRP sheets were studied. The experimental program includes testing twelve samples. Four samples served as control panels, while four samples were strengthened using CFRP sheets to study the effect of carbon sheets on the ultimate load capacity. Also, the four pretested control panels were also taken and rerepaired using CFRP sheets and retested for the purpose of evaluating their properties after repair. The ultimate load capacity, energy dissipation capacity, initial stiffness, and failure pattern were explained by the experimental results obtained. The experimental results revealed that the use of CFRP strips led to an improvement in the average ultimate loading capacity by 16.2% and 6.45% for the strengthening and repairing system, respectively. Also, the utilization of the CFRP strips as a strengthening system significantly improved the stiffness and the cracking load of RC two-way slabs. It was also noted that the ultimate loading capacity was proportionally related to the concrete strength for strengthened slabs with an increase of 23.3% for slabs with the highest concrete strength (C: 70).